2014
DOI: 10.1080/13596748.2014.955637
|View full text |Cite
|
Sign up to set email alerts
|

Outsiders within: isolation of international faculty in an American university

Abstract: As the internationalisation of higher education has become an important element in university global competitiveness, universities are engaged in initiatives to internationalise their curricula. Among the strategies employed to internationalise the campuses is the recruitment of highly skilled international faculty. The recruitment of such faculty is fraught with challenges of integrating and socialising the faculty into the academic ethos and social fabric of the university and community. This study presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
4
23
1
Order By: Relevance
“…Given the volatile nature of COVID-19 and its implications for all public and private institutions, including universities and colleges, it is highly likely that issues relating to connectedness while teleworking will remain relevant for the foreseeable future. As noted in previous research, faculty satisfaction has a strong influence on hiring and retaining high quality educators (Betts, 2009;Dolan, 2011;Golden, 2016;Lee, 2001;Munene, 2014;Ng, 2006). As discussed in previous research, and now as noted in this study following COVID-19, there are many challenges to feeling connected which seemed to impact faculty's overall job satisfaction.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Given the volatile nature of COVID-19 and its implications for all public and private institutions, including universities and colleges, it is highly likely that issues relating to connectedness while teleworking will remain relevant for the foreseeable future. As noted in previous research, faculty satisfaction has a strong influence on hiring and retaining high quality educators (Betts, 2009;Dolan, 2011;Golden, 2016;Lee, 2001;Munene, 2014;Ng, 2006). As discussed in previous research, and now as noted in this study following COVID-19, there are many challenges to feeling connected which seemed to impact faculty's overall job satisfaction.…”
Section: Resultssupporting
confidence: 64%
“…Faculty frequently discussed missing their colleagues and the social interactions that occurred when working at the university. They described telework as isolating and challenging, which was a challenge shared by remote faculty who participated in previous research related to inclusion and remote faculty (Golden, 2016;Munene, 2014).…”
Section: Developing a Sense Of Community While Teleworkingmentioning
confidence: 99%
“…According to OECD, highly-skilled migrants include highly skilled specialists, independent executives, and senior managers, specialized technicians or tradespersons, investors, business persons, "keyworkers" and sub-contract workers (Iredale 2001: 8). In general terms, all those individuals can be divided into business-oriented people (see Piekut 2013) and academics (see Skachkova 2007;Alberts 2008;Kreber -Hounsel 2014;Munene 2014). Academic studies reported that most of the problems common to both groups include limited interactions with colleagues and other local people, the language barrier, limited research funding, and cultural differences.…”
Section: Introduction: Highly Skilled Migrants In Slovakiamentioning
confidence: 99%
“…In a different study by Garson (2005), the author, an American expatriate, also described how she was informally excluded from a central network of colleagues at an Egyptian university. Similarly, in an American university, Munene (2014) identified problems related to isolation of the foreign faculty. We explore whether teacher-student relations could be one source of social support for expatriate academics, mitigating problems related to exclusion and isolation and leading to increased job satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An important reason for academics to travel between countries for work is the global competition for talent (Isakovic and Whitman, 2013;Silvanto and Ryan, 2014). Propelled by the desire to attain world-class status, many universities have embarked on ambitious and expensive programs of research and infrastructural advancement as well as curriculum development to meet international requirements (Munene, 2014;Trembath, 2016).…”
Section: Introductionmentioning
confidence: 99%